Hadronic jet physics and the quest for new matter in multi-jet final states with the ATLAS detector at the Large Hadron Collider - Nelson, M (2019)
The Standard Model of particle physics is one of the triumphs of contemporary science, but it is well-established that this theory must be incomplete. This thesis focuses on searching for the production of new matter, motivated by beyond-Standard Model framework of supersymmetry, with data recorded by the ATLAS experiment during Run 2 of the Large Hadron Collider. One of the crucial physics objects in the search for new matter described in this thesis is the hadronic jet. Before describing in detail the `multi-jets' search for new matter, which uses 36 fb−1 of ATLAS data in signal regions where at least 7 hadronic jets are required in the final state, the latest developments in hadronic jet physics at ATLAS shall be motivated and studied. Particular detail will be paid to new approaches in jet reconstruction, jet mass calculations and the corresponding jet mass resolution, and jet calibration at the energy and mass scales. Furthermore the issue of pileup contributions to hadronic jets shall be described, together with recent studies outlining how new developments in inputs to jet reconstruction and jet grooming can be used to improve the performance of hadronic jets in ATLAS and mitigate the effects of pileup therein. The full power of jet reconstruction at ATLAS will then be utilised in the multi-jets analysis. With the 36 fb−1 ATLAS data-set, no statistically significant evidence for new matter is reported, and new constraints on the mass of gluinos and stops are pushed up to 1.8 TeV and 1.4 TeV, at the 95 % confidence level, respectively (within the context of particular sets of new physics models). The multi-jets search is sensitive to final states with moderate ETmiss, and consequently is used to assess the LHC sensitivity to both R-parity-conserving (RPC) and R-parity-violating (RPV) supersymmetric scenarios. World-leading constraints across this `RPC-meets-RPV' spectrum will be assessed at the 95 % confidence level. Finally the ultimate plans for the full Run 2 iteration of the multi-jets analysis, amounting to 140 fb−1 of data, will be described.